Dopamine D2 Receptor-Mediated Modulation of Rat Retinal Ganglion Cell Excitability - Yin, Ning (Neurosci Bull, 2019)
Ganglion cells (RGCs) are the sole output neurons of the retinal circuity. Here, we investigated whether and how dopamine D2 receptors modulate the excitability of dissociated rat RGCs. Application of the selective D2 receptor agonist quinpirole inhibited outward K(+) currents, which were mainly mediated by glybenclamide- and 4-aminopyridine-sensitive channels, but not the tetraethylammonium-sensitive channel. In addition, quinpirole selectively enhanced Nav1.6 voltage-gated Na(+) currents. The intracellular cAMP/protein kinase A, Ca(2+)/calmodulin-dependent protein kinase II, and mitogen-activated protein kinase/extracellular signal-regulated kinase signaling pathways were responsible for the effects of quinpirole on K(+) and Na(+) currents, while phospholipase C/protein kinase C signaling was not involved. Under current-clamp conditions, the number of action potentials evoked by positive current injection was increased by quinpirole. Our results suggest that D2 receptor activation increases RGC excitability by suppressing outward K(+) currents and enhancing Nav1.6 currents, which may affect retinal visual information processing. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12264-019-00431-3) contains supplementary material, which is available to authorized users.